2010
DOI: 10.1162/jocn.2009.21321
|View full text |Cite
|
Sign up to set email alerts
|

Word Retrieval Failures in Old Age: The Relationship between Structure and Function

Abstract: Here, younger and older adults performed a picture naming task in the fMRI scanner. During successful naming, left insula activity was not affected by age or gray matter integrity. Age differences only emerged during TOTs, with younger but not older adults generating a "boost" of activity during TOTs compared to successful naming. Older adults also had less activity than younger adults during TOTs compared to "donʼt know" responses, and across all participants, less TOT activity was affiliated with lower gray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
80
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 45 publications
14
80
1
Order By: Relevance
“…Graph theory measures of functional connectivity during sentence comprehension were calculated using the weighted correlation method. (55). In whole-brain contrasts, older adults did not reliably activate any of the regions that younger adults engaged in response to TOTs.…”
Section: Language Functions Across the Adult Life Span: Evidence Frommentioning
confidence: 84%
“…Graph theory measures of functional connectivity during sentence comprehension were calculated using the weighted correlation method. (55). In whole-brain contrasts, older adults did not reliably activate any of the regions that younger adults engaged in response to TOTs.…”
Section: Language Functions Across the Adult Life Span: Evidence Frommentioning
confidence: 84%
“…2008), particularly in the left insula (Shafto et al. 2010), may have a role in preserving performance on phonological tasks in older individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest that the function of the left inferior parietal lobule might be to temporarily store phonological information in working memory (Fiez et al, 1996) and that the posterior dorsal part of the left inferior frontal gyrus might be specialized for processing phonological representations (Poldrack et al, 1999). As compared with orthographic and semantic processing, phonological processing was found to recruit more involvement of the left insula, the role of which has often been related to motor planning of articulation (Dronkers, 1996;Price, 2010;Wise et al, 1999) while other studies have also found its relationship with phonological retrieval deficits (Harasty et al, 2001;Shafto et al, 2007Shafto et al, , 2009. Although the functions of the left insula remain controversial, our results support its greater involvement in phonological processing as compared with other language-processing components.…”
Section: Divergent Regionsmentioning
confidence: 93%